Microstructure and mechanical properties of medium-carbon steel bonded on low-carbon steel by explosive welding. (5th January 2016) - Borchers, C.; Lenz, M.; Deutges, M.; Klein, H.; Gärtner, F.; Hammerschmidt, M.; Kreye, H.
Abstract: The mechanical properties of medium-carbon steel bond onto low-carbon steel by explosive welding are correlated to the microstructure of the steels. In the investigated weld there is a wavy interface including melt pockets exhibiting ultra-high hardness. It is found that the bonding is of high quality, reflected by the fact that in tensile testing with the bonding zone perpendicular to the tensile direction fracture happens in the medium-carbon steel. Graphical abstract: Highlights: Medium carbon steel was bonded onto low carbon steel by explosive welding. The bonding zone exhibits a wavy structure with melt pockets. The bonding zone shows very high hardness values. Fracture occurs in the low carbon steel upon tensile testing.